2021
DOI: 10.5194/se-12-713-2021
|View full text |Cite
|
Sign up to set email alerts
|

Seismic signature of the COVID-19 lockdown at the city scale: a case study with low-cost seismometers in the city of Querétaro, Mexico

Abstract: Abstract. Seismometers have detected the social response to lockdown measures implemented following the onset of the COVID-19 pandemic in cities around the world. This long-lasting pandemic has been a particular challenge in countries such as Mexico, where the informal economy constitutes most of the working population. This context motivated the monitoring of the mobility of populations throughout the various phases of lockdown measures independently of people's access to the internet and mobile technology. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The results showed rather good similarities between the noise and mobility data, indicating that the changes in seismic noise can be used to track the human activity in urban areas. We also observed a good match between the variation in seismic noise and data mobility's trends (Figure S4), confirming thus the previous results (Cannata et al, 2021;De Plaen et al, 2021;Diaz et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed rather good similarities between the noise and mobility data, indicating that the changes in seismic noise can be used to track the human activity in urban areas. We also observed a good match between the variation in seismic noise and data mobility's trends (Figure S4), confirming thus the previous results (Cannata et al, 2021;De Plaen et al, 2021;Diaz et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…However, people were allowed to go to the park for sports activities (e.g., running) during the lockdown, and the noise peaks observed on Saturday and Sunday mornings during the lockdown are related to such outdoor sports activities. To provide some insights into the causes of the noise changes during the lockdown, correlation between noise time series and community mobility data provided by Google and Apple was performed globally (Lecocq et al, 2020a) and at local scale (Cannata et al, 2021;De Plaen et al, 2021;Diaz et al, 2021). The results showed rather good similarities between the noise and mobility data, indicating that the changes in seismic noise can be used to track the human activity in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case for the city of Querétaro, where a low-cost Raspberry Shake network has been recently installed. The effect of the lockdown on seismic noise in this city has been analysed by De Plaen et al (2021). They also analysed the correlation of the median seismic rms with community mobility reported by Google.…”
Section: Discussionmentioning
confidence: 99%
“…We analyse the data for 2019 and 2020 up to 14 November to analyse the variations in the seismic noise as a response to the confinement measurements. Unfortunately, during the lockdown, some seismic stations malfunctioned, and it was not possible to service them (Pérez-Campos et al, 2021), resulting in a loss of real-time data.…”
Section: Datamentioning
confidence: 99%
“…Global government-imposed lockdowns to combat the COVID-19 pandemic have intensified the study of anthropogenic seismic noise, as the staggered easing of restrictions would aid the characterization of dominant noise sources. At the same time, the reduced noise levels during lockdowns make it possible to detect natural events that otherwise drown in the noise (De Plaen et al, 2021;Grecu et al, 2021) and thus improve seismic hazard estimates. Notably, in a global study of lockdown effects on seismic amplitudes, Lecocq, Hicks, et al (2020) also observed a significant reduction in seismic noise at 20 GSN stations.…”
Section: Environmental Seismology Beyond Global Networkmentioning
confidence: 99%